A five-pseudouridylation-associated-LncRNA classifier for primary prostate cancer prognosis prediction - Zheng, Pengxiang; Long, Zining; Gao, Anding; Lu, Jianming; Wang, Shuo; Zhong, Chuanfan; Lai, Houhua; Guo, Yufei; Wang, Ke; Fang, Chen; Mao, Xiangming (Frontiers in Genetics, 2023)
Prostate cancer (PCa) is one of the most common cancers in males around the globe, and about one-third of patients with localized PCa will experience biochemical recurrence (BCR) after radical prostatectomy or radiation therapy. A proportion of patients with BCR reportedly had unfavorable prognosis outcomes. Accumulative studies have shown that RNA modifications participate in the cancer-related transcriptome, but the role of pseudouridylation occurring in lncRNAs in PCa remains opaque. Therefore, we developed a classifier containing five pseudouridine-related lncRNAs to stratify PCa patients on BCR and named it the “ψ-lnc score.” We first separated the TCGA (The Cancer Genome Atlas Program) dataset into two subsets for training and testing. Kaplan-Meier survival analysis showed patients in the high ψ-lnc score group experienced BCR more than those in the low ψ-lnc score group. ROC (Receiver Operating Characteristic) curves demonstrated that ψ-lnc score outperformed other clinical indicators in BCR prediction. We validated our results with an external dataset, GSE54460, and likewise, the ψ-lnc score revealed its efficacy and authenticity. We constructed a ceRNA (competitive endogenous RNA) network to explore the model’s potential molecular functions and annotated it functionally through GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathways analysis. Lastly, we picked the only risk factor in the classifier, RP11-468E2.5, for further investigation, including pan-cancer analysis and experimental validation. Preliminarily, we confirmed RP11-468E2.5 as a tumor promoter. In aggregate, we offer some evidence that pseudouridylation in lncRNA participated in the development of PCa and provide a novel prognostic classifier for clinical practice.